A comprehensive review on graphene nanofluids: Recent research, development and applications. (1st March 2016) - Sadeghinezhad, Emad; Mehrali, Mohammad; Saidur, R.; Mehrali, Mehdi; Tahan Latibari, Sara; Akhiani, Amir Reza; Metselaar, Hendrik Simon Cornelis
Highlights: Recent advances in graphene nanofluids are reviewed. Reviews heat transfer and critical heat flux of graphene nanofluid. Identifies important results, inconsistence and contradictions of the topics. Needs in future research in this subject are discussed. Abstract: An overview of experimental results about the heat transfer capabilities of graphene nanofluids is reviewed. It shows that a number of publications are available on this issue and only few studies provide quantitative estimates on a complete set of experimental conditions so far. This research work includes experimental results about the capabilities of graphene nanofluids and summarizes the recent progress on preparation and evaluation methods, the ways to enhance the stability of graphene nanofluids and future applications in various fields of energy. Thermo-physical and optical properties of graphene nanofluids along with the heat transfer performance have also been reported in this review paper. Various challenges associated with the use of graphene nanofluids in actual applications has also been reported. It is expected that it could be a quick reference guide to have an overview of the different heat transfer phenomena in graphene nanofluids and the most essential parameters that influence the expected thermal performance of graphene nanofluids.